Feature-based sheet metal design and development system. (1st January 2000) - Lin, Zone-Ching; Horng, Jenn-Tsong
This study developed a feature-based design model to design sheet metal products, and achieve automatic product development to obtain the right size of sheet blanks. The focus of this paper is the integration of sheet metal design and development as a whole so as to ensure that the designed sheet metal products can be automatically developed. In terms of design, we adopted a feature-based design model. The system made use of the sheet metal product pattern provided by AMADA Company to extract a "face feature". Then, different face features were combined to design the necessary sheet metal products. The system observes the concept of "design for development" to establish the related data required by development during the design process so as to facilitate the development operations.